Pelatihan Pembuatan Dan Pelaporan Pajak UMKM Bagi Anggota Iwapi Kota Bandar Lampung - Maria Septijantini Alie; Umar Bakti; Iin Anita Agustinar (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Community service activities to provide knowledge about MSME tax preparation and reporting training. this activity was carried out on May 3 2023. The method of activity is with presentation of material, discussion, training and evaluation. a series of community service activities as follows: the implementing team presented material on the Basic Principles of Imposing Final MSME Income Tax, tax incentives provided by the government to MSME actors, Calculation and Payment of MSME Final Income Tax, and Reporting of MSME Income Tax and Tax Sanctions. The result of this community service activity is that activity participants are capable of making and reporting MSME taxes